От реальности к виртуальному миру и обратно: как язык помог нам в освоении Интернета и что произошло потом (на материале русского и польского языков) - Starodvorskaia, Ekaterina (Studia Rossica Posnaniensia, 2021)
The paper deals with the linguistic means that had helped us to adapt to virtual reality and that now seem to us to have existed always. The words and expressions didn’t appear out of nowhere – they were imported from our everyday language where they had been used for naming objects and processes in the real world. Thus the new realm, such as the physical one, was marked by language signs that determine the nature and the structure of our conception of the Internet which is interpreted generally as a physical space (different types of the latter). These signs are described here in terms of conceptual metaphor theory. Recently we have been dealing with some new, “web-born” expressions. It is shown that such expressions are no more limited to the describing of the Internet and are extended to the real world; it can be said they provide us with new tools to interpret the “old” reality. Thereby we can see the very moment when the source and the target domains (that is real and virtual worlds) are switching their places.